GATA6+ Peritoneal Resident Macrophage: The Immune Custodian in the Peritoneal Cavity - Jayakumar, Preethi; Laganson, Andrea; Deng, Meihong (Frontiers in Pharmacology, 2022)
Peritoneal resident macrophages (PRMs) have been a prominent topic in the research field of immunology due to their critical roles in immune surveillance in the peritoneal cavity. PRMs initially develop from embryonic progenitor cells and are replenished by bone marrow origin monocytes during inflammation and aging. Furthermore, PRMs have been shown to crosstalk with other cells in the peritoneal cavity to control the immune response during infection, injury, and tumorigenesis. With the advance in genetic studies, GATA-binding factor 6 (GATA6) has been identified as a lineage determining transcription factor of PRMs controlling the phenotypic and functional features of PRMs. Here, we review recent advances in the developmental origin, the phenotypic identity, and functions of PRMs, emphasizing the role of GATA6 in the pathobiology of PRMs in host defense, tissue repairing, and peritoneal tumorigenesis.